Religious Moderation in the Land of Syari'a: Christian Women's Resistance in Acehnese Education Institutions - Mustamar Iqbal Siregar; Bahtiar; Mhd Rasid Ritonga (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Aceh, as the region with the most absolute Muslim majority and the formal implementation of Islamic law in Indonesia, provides a unique context for studies on religious moderation. This study aims to explore the resistance strategies of Christian women in Aceh's educational institutions as an alternative lens to understand the dynamics of religious moderation. Framing the discussion within James C. Scott’s theory of public and hidden transcripts and supported by functionalist perspectives, this research highlights the functional resistance of Christian women in asserting their religious identity and their right to religious education. Utilizing a qualitative method with data gathered through interviews, observations, and documentation in Langsa and Banda Aceh, this study finds two forms of resistance: hidden resistance manifested in the veiling practices during the Sharia enforcement period and public resistance through open identity assertion and demands for religious education rights. These findings demonstrate that women, as social agents, play a crucial role in advancing religious moderation. The study recommends that governmental bodies, particularly the Ministry of Religious Affairs, formally recognize and empower women as key actors in promoting religious moderation across Indonesia.